Squirrels on skis ebook - Ray, J. Hamilton (Beginner Books., 2013)
This new Beginner Book about manic skiing squirrels—by J. Hamilton Ray with illustrations by Pascal Lemaitre—has the feeling of an old classic read-aloud. "Nobody knew how the mania grew. First there was one, and then there were two. Three more came gliding from under the trees. LOOK! On the hill. Those are squirrels on skis! Below lay the town, snow-covered and still. Not a sound could be heard. All was silent, until . . . Swwwishhhh swooped the skiers, all dressed for play. Eighty-five squirrels and more on the way!" As you can imagine, the townsfolk are NOT amused. Can intrepid reporter Sally Sue Breeze find out where the squirrels are getting their skis-and make them stop skiing long enough to eat lunch-before pest-control guy Stanley Powers sucks them up in his vacuum device? (Don't worry—Sally triumphs in a most unexpected way.) With delightfully understated, funny illustrations, this is the perfect book for beginning readers to curl up and chill out with on a snow day—or any day! Beginner Books are fun, funny, and easy to read! Launched by Dr. Seuss in 1957 with the publication of The Cat in the Hat , this beloved early reader series motivates children to read on their own by using simple words with illustrations that give clues to their meaning. Featuring a combination of kid appeal, supportive vocabulary, and bright, cheerful art, Beginner Books will encourage a love of reading in children ages 3–7.